Pengaruh Penerapan Model Role Playing Terhadap Civic Skills Peserta Didik Pada Pembelajaran PPKn - Mismiranda, Okta; Mariyani, Mariyani (University of Muhammadiyah Malang, 2024)
This research aims to determine the effect of the application of role playing learning models on the civic skills of students in PPKn learning at MA Al-Fatah Palembang. This research uses a quantitative approach with a quasi-experimental design method with a type of non-equivalent control group design consisting of an experimental class and a control class. The population in this study was the entire class XI with a total of 47 students, with a research sample of class XI MIA 1 and XI MIA 2 totaling 33 students taken using a non-probability technique type of purposive sampling. Data collection techniques are tests, likert scale questionnaires, and observations. Based on the results of this study that the application of role playing learning models affects the civic skills of students. This is evidenced based on the results of the hypothesis test using the independent sample t-test with the help of SPSS version 27, the significance value of intellectual skills data is 0.037 < 0.05 and participatory skills data significance value is 0.027 < 0.05. Thus, it can be concluded that there is an influence of the application of role playing learning models on the civic skills of students in PPKn learning at MA Al-Fatah Palembang.